THE FACTORS WHICH INFLUENCE THE QUALITY OF PROFIT (An Empirical Study on Non Financial Companies Listed in the Indonesia Stock Exchange) - Zalukhu, Rika Surianto (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to test the roomates factors influence the earnings quality. The research was done in the non-financial companies listed in BEI (Indonesia Stock Exchange) in 2016, based on the Fact Book published by the Stock Exchange. The main independent variables were the dividend (dividend-payingstatus), diversification (operatingdiversification status), and ownership of the firm (companyownership status). The dependent variable testedisearnings quality proxies by AAQ. AAQ had a negative correlation with the earnings quality. There are five control variables that also tested, namely PBV (External Growth Prospect), LEV (debt structure), AGE (Firm Maturity), HHI (Competitive Level in Industry), and CFO (Volatility of Operational Cash Flow). The results of the research demonstrated that the dividend-paying status had asignificantly negative influence on the earnings quality proxies(AAQ). The status of operational and geographic diversification had Significantly positive influence on the earnings quality proxies (AAQ). The research has failed to PROVE that the company ownership status had negatively influenced the earnings qualityproxies(AAQ). The results of the tests found out that dividend and diversification were proven to have information about quality profit. Therefore, they are supposed to be used as the indicators of the earnings quality. The research has failed to PROVE that the status of firm ownership had negatively influenced the earnings quality (AAQ). The results of the tests found out that dividend and diversification were proven to have information about quality profit. Therefore, they are supposed to be used as the indicators of the earnings quality. The research has failed to PROVE that the status of firm ownership had negatively influenced the earnings qualityproxies(AAQ).The results of the tests found out that dividend and diversification were proven to have information about quality profit. Therefore, they are supposed to be used as the indicators of the earnings quality.